The relationship between circadian blood pressure variability and maternal/perinatal outcomes in women with preeclampsia with severe features - Liuying Zhong; Wenfeng Deng; Weihan Zheng; Shuting Yu; Xiaosi Huang; Yaohong Wen; Philip C.N. Chiu; Cheuk-Lun Lee (Taylor & Francis Group, 2020)
Objective To determine whether circadian blood pressure (BP) variation of women with preeclampsia (PE) with severe features was associated with adverse maternal/perinatal outcomes. Methods 173 women with PE with severe features were recruitedand categorized into three groups: dipper, non-dipper and reverse dipper type BP group.. Maternal and perinatal outcomes were compared among groups. Results There were significant differences in gestational ages, premature delivery, retinopathy, HELLP syndrome, mean birth weight, rate of low birth weight infants and fetal growth restriction. Conclusion Aberrant circadian pattern of BP in women with PE with severe features was associated with several adverse maternal/perinatal outcomes.